The cAMP-dependent protein kinase downregulates glucose-6-phosphatase expression through RORα and SRC-2 coactivator transcriptional activity. (5th January 2016) - Madsen, Andre; Bjune, Jan-Inge; Bjørkhaug, Lise; Mellgren, Gunnar; Sagen, Jørn V.
Abstract: Fasting hormones activate the cAMP/PKA signaling pathway and stimulate expression of hepatic gluconeogenic enzymes including glucose-6-phosphatase (G6Pase). Previously it was shown that steroid receptor coactivator 2 (SRC-2) knock-out mice exhibit fasting hypoglycemia and that SRC-2 coactivates RAR-related orphan receptor alpha (RORα) at the proximal G6Pase promoter. We have investigated the upstream regulation and functional implications of this RORα/SRC-2 complex on G6Pase expression. In HepG2 cells, overexpression of the catalytic PKA subunit (PKA-Cα) reduced the SRC-2 protein level, recruitment to the G6Pase promoter, and its ability to coactivate RORα. Knock-down and transactivation experiments employing G6Pase promoter constructs demonstrated that RORα and SRC-2 are required for PGC-1α to stimulate G6Pase expression. These results suggest that PKA inhibits SRC-2 coactivation of RORα and in turn reduces PGC-1α dependent regulation of G6Pase. This indirect feedback mechanism may underlie the suppression of gluconeogenesis throughout long-term starvation. Highlights: RORα and its coactivator SRC-2 promote expression of hepatic G6Pase. RORα/SRC-2 facilitate PGC-1α dependent activation of the G6Pase promoter. Potent PKA activity causes degradation of SRC-2. PKA reduces recruitment of SRC-2 and RNA Polymerase II to the G6Pase promoter. This mechanism may suppress gluconeogenesis during long-term starvation.